2014
DOI: 10.1016/j.biomaterials.2013.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective ferulic acid (FA)–glycol chitosan (GC) nanoparticles for functional restoration of traumatically injured spinal cord

Abstract: An urgent unmet need exists for early-stage treatment of spinal cord injury (SCI). Currently methylprednisolone is the only therapeutic agent used in clinics, for which the efficacy is controversial and the side effect is well-known. We demonstrated functional restoration of injured spinal cord by self-assembled nanoparticles composed of ferulic acid modified glycol chitosan (FA-GC). Chitosan and ferulic acid are strong neuroprotective agents but their systemic delivery is difficult. Our data has shown a prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 52 publications
1
62
0
Order By: Relevance
“…Neuroprotective effect of these two flavonols is well established and the mechanism of action is believed to be their antioxidant activity and beneficial actions on brain cells which include positive effects on mood (Mandel and Youdim 2004; Nehlig 2013). Although neuroprotection by hydroxycinnamic acids can be much less as compared to catechins, the effect of trans -ferulic acid cannot be ruled out since it is reported to exert neuroprotective effect in in-vivo and in-vitro tests and its antioxidant capacity might be the contributing factor for such activity (Cheng et al 2008; Luo and Sun 2011; Wu et al 2014). The traditional use of date plam in headache prompted us to test the extracts for antinociceptive activity.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroprotective effect of these two flavonols is well established and the mechanism of action is believed to be their antioxidant activity and beneficial actions on brain cells which include positive effects on mood (Mandel and Youdim 2004; Nehlig 2013). Although neuroprotection by hydroxycinnamic acids can be much less as compared to catechins, the effect of trans -ferulic acid cannot be ruled out since it is reported to exert neuroprotective effect in in-vivo and in-vitro tests and its antioxidant capacity might be the contributing factor for such activity (Cheng et al 2008; Luo and Sun 2011; Wu et al 2014). The traditional use of date plam in headache prompted us to test the extracts for antinociceptive activity.…”
Section: Discussionmentioning
confidence: 99%
“…(i) Neuroprotective/neuroregenerative effect [84] (ii) Antitumoral activity [95] (iii) Antinflammatory and analgesic effect [96] (iv) Hemostatic activity [97] (v) Antimicrobial activity [98] In vitro studies on chitosan membrane showed its suitability as a substrate for proliferation, survival of Schwann cells as well as survival and differentiation of neuronal cells.…”
Section: Application Of Chitosan Membrane To Improve the Functional Rmentioning
confidence: 99%
“…PLGA-NPs and carboxymethylchitosan/polyamidoamine dendrimers loaded with MP have shown significant reduction in the lesion size, improved behavioral outcomes, suppression of microglial and astrocytic responses and improved axon regeneration in hemisection SCI models (84, 85). Systemic administration of ferulic acid (FA)- glycol chitosan (GC) (FA-GC) NPs was reported to cause improvements in locomotion, axonal and myelin protection, attributed to the neuroprotective properties of FA and GC which extend anti-oxidative effects to prevent inflammation and excitotoxicity (86). Administration of small molecule inhibitors such as Chicago sky blue, a macrophage migration inhibitory factor, encapsulated in NPs increased white matter and blood vessel integrity post-SCI (87), but demonstrated activation of both pro- and anti-inflammatory signals which could be ascribed to dynamic changes in macrophage phenotypes while still being reparative in nature (88).…”
Section: Drugs and Drug Delivery Systemsmentioning
confidence: 99%